Surveying the Landscape of Theories and Frameworks Used in the Study of Sport and Religion: An Interdisciplinary Approach - Zachary T. Smith; Steven N. Waller Ph.D. (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2018)
Religion and sport is a bourgeoning and maturing interdisciplinary area of study. As the volume of research conducted about topics related to the interface of religion and sport, attention to sound research methods, including the use of relevant theories and theoretical/conceptual frameworks becomes essential. Scholars such as Stausberg and Engler (2014) have posited that the methods used in religious studies (including theory and frameworks) are not as rigorous as those utilized in social science related fields. The imperative then becomes to use theories and frameworks from social science related disciplines such as leisure studies, sports studies and sport psychology to strengthen scholarship in this emerging area. The purpose of this paper is to provide a review of pertinent theories and theoretical/conceptual frameworks that are commonly used in the study of sport and religion. An interdisciplinary approach is taken to highlighting and expounding on a select group of theories and theoretical/conceptual frameworks.
Keywords: Theory; theoretical frameworks; leisure; religion; sport